The Role of Cognitive and Affective Post-Purchase Dissonance as Mediating Variables between Perceived Impulsiveness and Repurchase Intention - Octavianus, Steven; Aprillia, Ariesya (Pandawan, 2025)
The study investigates whether cognitive and affective post-purchase dissonance mediate the relationship between perceived impulsiveness and repurchase intention. Using purposive sampling, data were collected from 220 respondents, predominantly women with bachelor’s degrees. The study applied Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. The findings indicate that cognitive and affective post-purchase dissonance do not function as mediators in the relationship between perceived impulsiveness and repurchase intention. Practical implications of the study suggest that companies, especially e-commerce platforms, should focus on minimizing post-purchase dissonance to enhance customer satisfaction and retention. Strategies such as streamlined product return policies and responsive customer service can play a vital role in achieving this. These measures can help address consumer doubts and negative emotions following impulsive purchases, fostering greater trust and loyalty. This research contributes to the understanding of consumer behavior in online retail but highlights the need for further exploration using mixed methods to better capture the emotional nuances of post-purchase dissonance. Additionally, expanding the scope to include diverse products and demographics could enrich future findings.